Financial and Actuarial Statistics, 2nd Edition - Borowiak, Dale; Shapiro, Arnold (Chapman and Hall/CRC, 2013)
Understand Up-to-Date Statistical Techniques for Financial and Actuarial ApplicationsSince the first edition was published, statistical techniques, such as reliability measurement, simulation, regression, and Markov chain modeling, have become more prominent in the financial and actuarial industries. Consequently, practitioners and students must ac.